Solution of Dual Integral Equations Involving Generalized Function: Solving Dual Integral Equations through Mellin Transform and Polynomial Function Kernel (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This article's main goal is to solve a dual integral equation by lowering it to an integral equation through the use of mellin transform whose kernel includes generalized polynomial function. We assume that there are definitely many ways to reduce these dual integral formulas by using various transformations such as Fourier, Henkel, etc. For the reason of illustration we pick a dual integral equation of particular type and reduced it, by use of fractional operators and Mellin transform, to an integral equation.